SISTEM PENUNJANG KEPUTUSAN PEMILIHAN HOTEL DI KOTA TANJUNGPINANG DAN PULAU BINTAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Adisaputra, Winarta -; ELISA, ERLIN (Computer Science and Industrial Engineering, 2021)
In this study, the author aims to design build a support system for decision-making on hotel selection in Tanjungpinang City and Bintan Island. The method I use is the Simple Additive Weighing (SAW) method. The authors use five criteria. That is, hotel room rental prices, hotel location, hotel cleanliness, hotel comfort, hotel services. The use of the Decision Support System (DSS) is expected to help in making the decision to choose the best hotel in Tanjungpinang City and Bintan Island, given that no specific hotel selection method has been used so far so that sometimes decisions can be made. are considered less objective than targeted. During this study, a case will be assigned, that is, looking for the best alternative based on pre-determined criteria using the Simple Supplement Weighting (GDP) method. The survey was conducted by searching for the value of weight for each feature, followed by a ranking process that would determine the optimal alternative, namely the best hotels in Tanjungpinang City and Bintan Island. The results obtained are hotel selection Decision Support System which are able to assist visitors to choose hotels among the numerous numbers of hotels in Tanjungpinang City and Bintan Island.